Night diver - Lowell, Elizabeth, 1944- (William Morrow, an Imprint of HarperCollinsPublishers, 2014)
Former British military diver Holden Cameron must investigate the suspicious activity surrounding a Donnelly dive to recover treasure from the ancient wreck of a pirate ship located near St. Vincent. When equipment, treasure, and even divers begin to disappear, owner Kate Donelly and Holden form an uneasy alliance to uncover the truth. But the deeper they plummet into the mystery, the closer they come to each other. Soon they are sharing their deepest fears and darkest secrets --and a combustible chemistry too hot to ignore.